Buscando ganhos de competitividade através da logística reversa: oportunidades na indústria de tabaco - Lima, Adrielle Ferreira Gomes de (Universidade Federal de São Carlos, 2024)
The tobacco market in Brazil presents continuous expansion, and faces, in addition to competition, several legislative restrictions that may represent barriers in the negotiation with retailers. The Reverse Logistics represents an efficient politics responsible for generating value for the client and competitive advantage for the company. Thus, investing in reverse flow politics of the aftermarket, that is, stimulating the return of unsold items, proves to be an attractive tool in the relationship with new customers. Therefore, the objective of this research is to evaluate the competitiveness gains that the reverse logistics of aftermarket can provide to retailers and the distribution network that supplies them. The present research is a case study, applied to the relationship between the agents that act in the distribution and return of a large tobacco industry. It is an exploratory research type, of an applied nature with a combined approach (quantitative and qualitative). Thus, the research instruments used were the analysis of documents and performance indicators, as well as the application of an online questionnaire to a previously selected sample and, finally, the direct and participant observation of the object of study. The results obtained demonstrated that there is a well-defined reverse flow policy, with competitive benefits observed such as a guarantee of a positive corporate image, increased competitiveness and market share, and differentiation of services were identified by the interlocutors, that benefits both sides involved.
Searching competitiveness gains through reverse logistics: opportunities in the tobacco industry
Keywords: Logística Reversa; Pós-venda; Tabaco; Competitividade; Varejo; Reverse Logistics; Post sell; Tobacco; Competitiveness; Retail; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO